2019
DOI: 10.1016/j.bbr.2019.112082
|View full text |Cite
|
Sign up to set email alerts
|

Put on your (fNIRS) thinking cap: Frontopolar activation during augmented state creativity

Abstract: Highlights  To 'think creatively' on demand is an augmented state of creativity  Creativity can be indicated using the semantic distance between noun-verb pairs  When cued to 'think creatively', semantic distance scores are higher than when uncued  Cued and uncued responses indicate regional left frontopolar activity using fNIRS  Use of fNIRS during augmented creativity states in naturalistic settings is supported

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Importantly, our data show that the fMRI correlates of egocentric interference include parts of the mirror neuron system (middle and superior precentral gyri) as well as left frontopolar cortex known to be involved in deductive reasoning 37 . In particular, this latter area was associated with analogical reasoning and relational cognition, two cognitive processes involved in self-other distinction, decentering and inferential process 38 . Moreover, a recent EEG study showed that left frontopolar theta activity is associated with planning performance and successfully generated self-plans pointing to its role in the construction of self-centered cognitive processes 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our data show that the fMRI correlates of egocentric interference include parts of the mirror neuron system (middle and superior precentral gyri) as well as left frontopolar cortex known to be involved in deductive reasoning 37 . In particular, this latter area was associated with analogical reasoning and relational cognition, two cognitive processes involved in self-other distinction, decentering and inferential process 38 . Moreover, a recent EEG study showed that left frontopolar theta activity is associated with planning performance and successfully generated self-plans pointing to its role in the construction of self-centered cognitive processes 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The Biographical Inventory of Creative Behaviors (BICB), developed by Batey (2007), has emerged as one of the more popular self-report tools to measure everyday creativity. It is cited and discussed in many major reviews of self-report tools in creativity research (Kaufman, 2019;Puryear et al, 2017;Said-Metwaly et al, 2017;Silvia et al, 2012) and has been used in research on wide-ranging topics in creativity studies (e.g., Tempest & Radel, 2019;West & Somer, 2020). To date, however, the BICB has yet to receive a detailed psychometric evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…First, because fNIRS data contain various kinds of noise, we performed preprocessing using open POTATo (Yamada et al ., 2012). The preprocessing steps are as follows: 1) short distance processing (opSSR) was done to remove skin blood flow changes; 2) bandpass filtering (0.01-0.5 Hz) using an FFT (Band Filter) was performed (Tempest and Radel, 2019); and 3) the overall data for each participant was corrected with Rest-1 as baseline and all times were calculated into Z-scores for each participant (Ono, 2019). After preprocessing, the average value for 30 seconds during the task was used as the representative value for paired t-tests.…”
Section: Methodsmentioning
confidence: 99%